Proyecto de aula para el desarrollo de competencias científicas en la enseñanza de los conceptos de genotipo y fenotipo (2021)
The teaching of basic concepts of genetics is extremely important when it comes to address these contents in the classroom, because it allows to achieve a better understanding of the topics and problem-situations that arise. In the current classroom project two educational units are developed based on Jerome Bruner’s active discovery learning model, seeking to generate skills in the students and indeed the development of scientific competences. This classroom project was applied to eight grade students of the Educational Institution Luis López de Mesa in the municipality of Guadalupe, where the school garden is used as a mean of teaching-learning, this allows to the students work from the rural context, taking in account that the teaching of natural science must be linked to nature as such, since it is from this where the knowledge is obtained for being apply to real life. Key words: Discovery Learning, school garden, scientific competences, basic concepts of genetics.